2020
DOI: 10.3390/diagnostics10080606
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Roles of PTTG1 and PTTG2 Genes and Pseudogene PTTG3P in Head and Neck Squamous Cell Carcinomas

Abstract: Background: Head and neck squamous cell carcinomas are a group of heterogeneous diseases that occur in the mouth, pharynx and larynx and are characterized by poor prognosis. A low overall survival rate leads to a need to develop biomarkers for early head and neck squamous cell carcinomas detection, accurate prognosis and appropriate selection of therapy. Therefore, in this paper, we investigate the biological role of the PTTG3P pseudogene and associated genes PTTG1 and PTTG2 and their potential use as biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In HNC, some pseudogene transcripts have been studied and associated with tumor aggressiveness, HPV16 infection, and prognosis [24][25][26][27][28]. However, their role in HNC remains poorly explored, while patients' therapy resistance and poor survival rates highlight the need of finding novel molecular biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HNC, some pseudogene transcripts have been studied and associated with tumor aggressiveness, HPV16 infection, and prognosis [24][25][26][27][28]. However, their role in HNC remains poorly explored, while patients' therapy resistance and poor survival rates highlight the need of finding novel molecular biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on The Cancer Genome Atlas (TCGA) data and the University of Alabama Cancer Database (UALCAN), Grzechowiak et al [27] described that PTTG3P (pituitary tumor-transforming 3 pseudogene) pseudogene transcript abundance was correlated with HNC lower T-stage (T1 or T2), positive HPV16 status, and poor prognosis [27]. Gene Set Enrichment Analysis indicated that PTTG3P was correlated with genes involved in DNA repair, oxidative phosphorylation, and peroxisome pathways [27].…”
Section: Hnc In Generalmentioning
confidence: 99%
“…PTTG was originally separated from the tumor of the pituitary tumor, a multi-function protein, involved in cell cycle, cell proliferation, angiogenesis, and metastasis [4]. PTTG consistins of two genes with protein products PTTG1 and PTTG2, and a processed pseudogene PTTG3P, has been described in the context of carcinogenesis [5]. Overexpression of PTTG was reported in many cancers including lung, gastric, kidney, pancreatic, breast cholangiocarcinoma, psoriasis, Adrenocortical Carcinomacarcinoma, hepatocellular carcinoma, glioblastoma, esophageal squamous cell carcinoma, and prostate cancer [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…PTTG1, described in the context of carcinogenesis [13][14][15][16], as a target gene of E2F family [17,18] has been implicated in multiple cellular processes including, but not limited to, cellular differentiation, apoptosis, DNA damage repair, maintains chromosomal stability and angiogenesis in breast cancer [19][20][21]. Quiet a lot of breast cancer patients couldn't bene ted from NACT and show distinct responses to NACT even when their clinicopathological characteristics are same or similar because of the molecular differences, and the absence of well-de ned molecular target [22,23].…”
Section: Introductionmentioning
confidence: 99%